Criança, narrativa e amor: os vínculos afetivos em Sakura Card Captors - Santilli, Ana Catarina (2018)
According to Jerusa Pires Ferreira’ studies, popular myths and tales always had a great role in the storage and transmission of elements of a culture. However, due to parents' lack of time, there is no longer a tradition of telling stories to children, and the main sources of these stories end up being the audio-visual animations shown on children's channels or on internet video sites. The problem is, as Norval Baitello Júnior and Vicente Romano noticed, more and more people relate to media images and stop being connected with other bodies, which can decrease sensitivity to deal with others. This becomes more alarming when we realize the contents produced for children, who are in a formation phase, in which they most need affection. From a research by Jo Groebel, it was noticed that children turn to media heroes as role models to help them cope with difficult situations. However, many of these heroes resolve their conflicts aggressively, and pass on the message that there are bad people who should be eliminated, which often generates tension and anxiety. From there, this research has an interest to study how a children's audiovisual narrative can treat love in a way that sensitizes the child to the other and to the important gestures in human bonding. In this case, love is understood as a personal bond that unites one human being to another. For this purpose, the animation Sakura Card Captors was chosen as the study corpus. It is a Japanese children's cartoon, appeared in Brazil in the early 2000s, and it was very successful among the public. It is a narrative that explores a great variety of affective bonds between the characters, in many scenes of banal moments, but in which the small gestures used to deal with the others are perceptible. Starting from the works of the ethologists Boris Cyrulnik and Irenäus Eibl-Eibesfeldt about love, and from the studies of the infant psychoanalyst Bruno Bettelheim on narratives for children, this research intends to throw a phenomenological view on the object, making an analysis of the narrative from the links between the characters. The intention is to check the types of love present in the cartoon, according to the classification of affective systems made by Harry Harlow, and to observe how the characters affect each other during the story. It was interesting to note that the animation is able to explore a series of bonds that children form during their lives, emphasizing some daily life details important to the connection with people and the world